Acute inflammatory, anthropometric, and perceptual (muscle soreness) effects of postresistance exercise water immersion in junior international and subelite male volleyball athletes - Horgan, B. G.; West, N. P.; Tee, N.; Drinkwater, E. J.; Halson, S. L.; Vider, J.; Fonda, C. J.; Haff, G. G.; Chapman, D. W. (The Journal of Strength and Conditioning Research, 2022)
Athletes use water immersion strategies to recover from training and competition. This study investigated the acute effects of postexercise water immersion after resistance exercise. Eighteen elite and subelite male volleyball athletes participated in an intervention using a randomized cross-over design. On separate occasions after resistance exercise, subjects completed 1 of 4 15-minute interventions: control (CON), cold water immersion (CWI), contrast water therapy (CWT), or hot water immersion (HWI). Significance was accepted at p = 0.05. Resistance exercise induced significant temporal changes (time effect) for inflammatory, anthropometric, perceptual, and performance measures. Serum creatine kinase was reduced (g = 0.02-0.30) after CWI (p = 0.007), CWT (p = 0.006), or HWI (p < 0.001) vs. CON, whereas it increased significantly (g = 0.50) after CWI vs. HWI. Contrast water therapy resulted in significantly higher (g = 0.56) interleukin-6 concentrations vs. HWI. Thigh girth increased (g = 0.06-0.16) after CWI vs. CON (p = 0.013) and HWI (p < 0.001) and between CWT vs. HWI (p = 0.050). Similarly, calf girth increased (g = 0.01-0.12) after CWI vs. CON (p = 0.039) and CWT (p = 0.018), and HWI vs. CON (p = 0.041) and CWT (p = 0.018). Subject belief in a postexercise intervention strategy was associated with HSP72 ("believer">"nonbeliever," p = 0.026), muscle soreness ("believer">"nonbeliever," p = 0.002), and interleukin-4 ("nonbeliever">"believer," p = 0.002). There were no significant treatment × time (interaction effect) pairwise comparisons. Choice of postexercise water immersion strategy (i.e., cold, contrast, or hot) combined with a belief in the efficacy of that strategy to enhance recovery or performance improves biological and perceptual markers of muscle damage and soreness. On same or subsequent days where resistance exercise bouts are performed, practitioners should consider athlete beliefs when prescribing postexercise water immersion, to reduce muscle soreness.